Contextualising COPD self-management in Malaysia: insights from a qualitative photo-elicitation study of patients-caregiver dyads - Salim, Hani; Fatin-Syazwani, Abd Malek; Zakaria, Natrah; Mohamad Yatim, Sa’ari; Chandrabose, Thanalactchumy; Ramdzan, Siti Nurkamilla; Chan, Soo Chin; Mohamad, Fadzilah; Shariff Ghazali, Sazlina (University of Edinburgh, 2025)
Background Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality and morbidity globally, disproportionately affecting low- and middle-income countries (LMICs). Despite pulmonary rehabilitation (PR) being a key intervention, uptake and adherence remain low due to economic, geographical, and sociocultural barriers. We explored the lived experiences of individuals with COPD and their caregivers in Malaysia to identify contextually grounded self-management strategies. Methods We employed a qualitative photo-elicitation approach between January and December 2024. We purposively sampled adults with COPD and their caregivers based on age, gender, and ethnicity from a hospital-based outpatient PR centre in Selangor, Malaysia. We conducted semi-structured dyadic interviews at two time points. Participants documented their experiences through photographs, which guided the discussions. Lastly, we transcribed the interviews verbatim and thematically analysed them. Results Nine dyads (participant-caregiver pairs) completed two interviews. Participants were men with a mean age of 65.3 (standard deviation (SD) = 3), with GOLD stage 3–4. Caregivers were women, with a mean age of 56.4 (SD = 11). Six dyads identified themselves as Malay ethnicity. Four themes emerged: Navigating economic constraints in COPD self-management, where participants substituted costly devices with low-cost tools (e.g. loaded trolleys); Culturally embedded self-management: integrating practices like Qigong and reframing daily chores (e.g. folding laundry) as rehabilitation; Technology as a tool for home-based COPD care with participants adapting exercises from internet (e.g. Facebook) while caregivers expressed concerns over unverified content; and Family as partners in COPD management, where caregivers not only monitored symptoms but also exercised alongside participants, reporting mutual health benefits. These strategies were seen as essential for sustaining engagement in COPD care. Conclusions Photo-elicitation and dyadic interviews revealed how cultural traditions, digital adaptations, and reciprocal caregiving intersect in everyday life, shaping COPD self-management in low-resource settings. Interventions should build on these lived strategies, prioritising context-sensitive, low-cost, and inclusive care models for COPD in LMICs.